Mechanisms that influence accuracy of the soccer kick - Katis, A.; Giannadakis, E.; Kannas, T.; Amiridis, I.; Kellis, E.; Lees, A. (Journal of Electromyography and Kinesiology, 2013)
Goal scoring represents the ultimate purpose of soccer and this is achieved when players perform accurate kicks. The purpose of the present study was to compare accurate and inaccurate soccer kicks aiming to top and bottom targets. Twenty-one soccer players performed consecutive kicks against top and bottom targets (0.5 m2) placed in the center of the goal. The kicking trials were categorized as accurate or inaccurate. The activation of tibialis anterior (TA), rectus femoris (RF), biceps femoris (BF) and gastrocnemius muscle (GAS) of the swinging leg and the ground reaction forces (GRFs) of the support leg were analyzed. The GRFs did not differ between kicking conditions (P > 0.05). There was significantly higher TA and BF and lower GAS EMG activity during accurate kicks to the top target (P < 0.05) compared with inaccurate kicks. Furthermore, there was a significantly lower TA and RF activation during accurate kicks against the bottom target (P < 0.05) compared with inaccurate kicks. Enhancing muscle activation of the TA and BF and reducing GAS activation may assist players to kick accurately against top targets. In contrast, players who display higher TA and RF activation may be less accurate against a bottom target. It was concluded that muscle activation of the kicking leg represents a significant mechanism which largely contributes to soccer kick accuracy.